MICROMORPHOLOGY, AND PRELIMINARY PHYTOCHEMICAL SCREENING OF SPIROSTACYS AFRICANA L. LEAF AND BARK. - Singh, Karishma; Baijnath, Himansu (Student's Journal of Health Research Africa, 2024)
Background: Spirostachys africana is indigenous to Southern Africa and is often widely used in African traditional medicine. The utilization of this species has been investigated for its medicinal properties. However, the current investigation aimed to analyze the micromorphology of S. africana leaves and at the same time screen for the presence of secondary metabolites in the leaf and latex extracts. Methods: Stereomicroscopy and scanning electron microscopy were used to study morphological characters of both the abaxial and adaxial surfaces of S. africana leaves. Phytochemistry screening was performed using a standard protocol involving chemical reagents and a series of reactions to determine the presence of the phytochemical compound classes. Results: It was found that S. africana leaves possess both non-glandular and glandular trichomes on the adaxial surface, and no trichomes on the abaxial surface of the leaves. The phytochemical analysis revealed that the latex crude extract contains six phytochemical classes (alkaloids, steroids, flavonoids, coumarins, saponins, terpenoids) while the leaf crude extract contains seven phytochemical classes (alkaloids, phenols, flavonoids, coumarins, saponins, terpenoids, tannins). Conclusion: The micromorphological analysis of Spirostachys Africana leaf and bark provided valuable insights into their structural characteristics, revealing unique features such as thick cuticles, trichomes, and distinctive epidermal cells that are likely to play crucial roles in the plant's defense mechanisms and ecological adaptations. Preliminary phytochemical screening further identified the presence of key bioactive compounds. These findings not only corroborate the traditional uses of S. africana in herbal medicine but also highlight its potential for pharmacological applications. Recommendations: The identification of the bioactive compounds lays a foundational framework for future studies aimed at exploring the therapeutic potential and bioactivity of S. africana, thereby contributing to the broader understanding of its medicinal properties and promoting the sustainable use of this Indigenous species.